"It was different because I was a man": A qualitative evidence synthesis exploring the lived experiences of adult male survivors of female-perpetrated intimate partner abuse. (November 2022) - Richardson, Hollie; Kloess, Juliane A.
Abstract: Between 2018 and 2019, approximately four in 100 men experienced intimate partner abuse (IPA) in England and Wales. The impact of IPA can be severe and pervasive, including physical and mental health difficulties. There are currently few studies exploring the experiences and needs of adult male survivors of IPA, with a large proportion of the literature focusing on the victimization of women. A literature review in the form of a synthesis of qualitative research exploring the experiences of adult male survivors of IPA was therefore completed. 12 studies using a range of qualitative methodologies were included in the review. Original extracts from the data, as well as the first author's interpretations, were included in the synthesis to identify common themes and concepts across the studies. Five superordinate themes were identified. The concept of 'hegemonic masculinity' was present within all of these themes. The review presented here highlights the types of abuse men experience, how they try to make sense of and cope with these, the process of help-seeking, and the way in which societal views of masculinity color their experiences. These themes illustrate the significant impact IPA can have on men, and how their experiences compare to those of adult female survivors of IPA. Highlights: A synthesis of qualitative research exploring the experiences of male survivors of IPA We explore the way in which societal views of masculinity color these experiences. We compare the experiences of male and female survivors of IPA. We discuss the societal beliefs which keep this population hidden.